Implementation of Inventory Checking System Using Finite State Machine in Role Playing Game - Kusuma, Ahmad Fauzi Anggi Ariesta; Handayani, Riska Dwi (International Journal of Computer and Information System (IJCIS), 2024)
This study aims to implement an inventory checking system combined with Finite State Machine (FSM) in the Role Playing Game (RPG) game genre using Arnold Hendrick's Game Development Life Cycle (GDLC) development method. In RPG games, inventory management is a crucial aspect that affects the gameplay, especially in the management of quests and item crafting features. The FSM approach is used to manage state and state transitions in randomly completed quests, providing more flexible dynamics in the completion of in-game tasks. The GDLC method was chosen to ensure that system development is carried out in a structured manner, starting from planning, design, implementation, to testing. This research integrates FSM in  the RPG Maker MV game engine, which allows developers to dynamically set various quest variables and optimize the item crafting process. By implementing FSM, items can be combined based on predefined state conditions, creating a more complex and interactive gameplay experience. The results of this study show that the application of FSM in the inventory checking system has a significant impact on flexibility in quest management and crafting. Quest variables that can be completed freely according to the player's choice, Overall, Finite State Machine can provide interactivity and depth of gameplay in RPGs with various quests that are tiered with each level, especially in the use of RPG Maker MV as an engine to apply various supporting variables to create flexibility in completing missions.